Nonverbal Communication in the Minangkabau Marosok Tradition: An Analysis of Symbols and Ethical Values from an Islamic Economic Perspective - Siska Putri; Rizal Fahlefi; Azifah Hidayati; Ahmad Lutfi (Yayasan Mitra Peduli Indonesia, 2026)
This study aims to explore the meaning of nonverbal communication in the Minangkabau marosok tradition and examine how Islamic economic values are embodied within it. Marosok is a traditional livestock trading practice conducted discreetly through hand symbols hidden beneath a sarong, functioning as a silent transactional language. The research employs a phenomenological qualitative approach with ethnographic nuances, utilising field observation, in-depth interviews, and documentation in the livestock markets of Cubadak, Sungai Sariak, and Payakumbuh. The findings reveal that the hand symbols and sarong serve not only as tools of economic communication but also as representations of the moral and spiritual values of Minangkabau society. Each transaction is guided by the principles of honesty (ṣidq), trustworthiness (amānah), and mutual consent (tarāḍin) that shape social relationships among market actors. This tradition reflects the practical implementation of Islamic economic values such as ‘adl (justice), ta‘āwun (mutual support), and hifz al-māl (protection of wealth) within a local cultural context rooted in the philosophy adat basandi syarak, syarak basandi Kitabullah. The findings affirm that marosok represents a community-based, trust-driven economic model capable of maintaining efficiency, fairness, and ethical integrity without reliance on formal systems. Thus, the marosok tradition offers valuable insights for strengthening contemporary Islamic economic practices grounded in local wisdom.